2015
DOI: 10.1101/gad.265629.115
|View full text |Cite
|
Sign up to set email alerts
|

Local regulation of the Srs2 helicase by the SUMO-like domain protein Esc2 promotes recombination at sites of stalled replication

Abstract: Accurate completion of replication relies on the ability of cells to activate error-free recombination-mediated DNA damage bypass at sites of perturbed replication. However, as anti-recombinase activities are also recruited to replication forks, how recombination-mediated damage bypass is enabled at replication stress sites remained puzzling. Here we uncovered that the conserved SUMO-like domain-containing Saccharomyces cerevisiae protein Esc2 facilitates recombination-mediated DNA damage tolerance by allowing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 51 publications
(83 reference statements)
5
96
0
Order By: Relevance
“…The finding that AGO proteins bind to SIM raised the possibility that AGO has SUMO-like domains found to be present in a few proteins [72,73]. However, analysis suggested that such domains are absent in AGO proteins.…”
Section: Potential Sim-binding Sites In Ago2mentioning
confidence: 99%
“…The finding that AGO proteins bind to SIM raised the possibility that AGO has SUMO-like domains found to be present in a few proteins [72,73]. However, analysis suggested that such domains are absent in AGO proteins.…”
Section: Potential Sim-binding Sites In Ago2mentioning
confidence: 99%
“…With the demonstration of the strippase activity, many of the phenotypes of srs2 mutants could be interpreted as a failure to prevent homologous recombination (HR), during both repair and rescue of stalled replication forks (Barbour and Xiao 2003;Watts 2006;Lambert et al 2010) and in other instances of mitotic HR (Robert et al 2006;Le Breton et al 2008;Burgess et al 2009;Kerrest et al 2009;Urulangodi et al 2015). The DNA helicase unwinding activity in vivo was demonstrated to be necessary to counteract the deleterious consequences of trinucleotide repeat sequences that could form stable hairpin structures during replication Lahue 2004, 2005;Kerrest et al 2009) and in unwinding at lesion sites produced by cleavage at rNMP residues in DNA to limit mutagenesis (Potenski et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…7 Mechanistically, we found that Esc2 preferentially binds structures arising at stalled and damaged replication forks. In this environment, Esc2 engages via its SLDs in regulatory interactions with SIM-containing replisome-associated proteins.…”
Section: Sumo-mediated Global and Local Control Of Recombinationmentioning
confidence: 81%
“…3,4 Our recent findings identified a mechanism that guides recombination specifically at sites of replication stress, by opposing Srs2 accumulation. 7 This newly identified mechanism is also SUMO-orchestrated, involving SIM/SLD interactions between the SIM motifs of Srs2 and STUbL components and the SLDs of Esc2. Our results indicate that the SLD/SIMcoordinated regulatory mechanism acts to locally curb down the anti-recombination effect caused by SUMOylated PCNA, enabling recombination-mediated DDT at sites of replication stress (Fig.…”
Section: Sumo-mediated Global and Local Control Of Recombinationmentioning
confidence: 99%
See 1 more Smart Citation